2013
DOI: 10.1212/wnl.0b013e3182929fd5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 4-aminopyridine on vision in multiple sclerosis patients with optic neuropathy

Abstract: Objective: The objective of this randomized, double-blind, placebo-controlled, crossover study was to examine if patients with optic neuropathy would derive a therapeutic benefit from 4-aminopyridine (4-AP) treatment. Furthermore, the study was intended to determine if patients with certain P100 latencies or retinal nerve fiber layer (RNFL) measures would be more likely to respond to therapy.Methods: Patients were enrolled in a randomized, placebo-controlled, double-blind, crossover study of 10 weeks duration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…Eight of 28 eyes treated with 4-AP showed improvement in LCVA compared with three of 28 placebo eyes, though there was no group difference. VEP latency improved in the 4-AP group but declined in the placebo group, and this beneficial effect was more pronounced in eyes with less RNFL thinning (ie, less optic nerve axonal loss) 49. 4-AP has also shown beneficial effects on nystagmus,50 as have other agents.…”
Section: Positive Consequence Of Ms Medicationsmentioning
confidence: 89%
“…Eight of 28 eyes treated with 4-AP showed improvement in LCVA compared with three of 28 placebo eyes, though there was no group difference. VEP latency improved in the 4-AP group but declined in the placebo group, and this beneficial effect was more pronounced in eyes with less RNFL thinning (ie, less optic nerve axonal loss) 49. 4-AP has also shown beneficial effects on nystagmus,50 as have other agents.…”
Section: Positive Consequence Of Ms Medicationsmentioning
confidence: 89%
“…While Ruck et al. (2014) did not observe any beneficial effects after dalfampridine treatment, three additional studies reported improvements after 4‐aminopyridine treatment in MS patients (Davis, Stefoski, & Rush, 1990; van Diemen et al., 1993; Horton et al., 2013). In our patient cohort, no beneficial effect of dalfampridine treatment was detected in the overall cohort.…”
Section: Discussionmentioning
confidence: 99%
“…However, regarding the assumed effects on conduction, action‐potentials, and synaptic and neuromuscular transmission, it would be very likely that the compound also has an effect on other parts of the central nervous system and therefore on other neurological functions such as vision, fatigue, or cognition (Kim, Goldner, & Sanders, 1980; Shi & Blight, 1997; Smith, Felts, & John, 2000). Indeed, studies investigating whether or not dalfampridine or 4‐aminopyridine exert beneficial effects on other neurological function in MS patients described positive effects on measures of cognitive function, upper limb function, fatigue, and vision (Horton et al., 2013; Jensen, Ravnborg, Mamoei, Dalgas, & Stenager, 2014; Limone, Sidovar, & Coleman, 2013; Magnin et al., 2015; Pavsic, Pelicon, Ledinek, & Sega, 2015; Prugger & Berger, 2013; Rossini et al., 2001; Ruck et al., 2014). …”
Section: Introductionmentioning
confidence: 99%
“…We designed inclusion criteria to ensure that patients had demyelinating injury in the visual pathway (VEP P100 latency in at least one eye of 118 ms) and to increase the likelihood that the number of surviving axons was sufficient to provide the needed substrate for remyelination to occur (approximated by retinal nerve fibre layer thickness on spectral-domain optical coherence tomography [OCT] >70 µm in the VEP qualifying eye). Exclusion criteria included confounding ophthalmological disease that could affect vision or testing, changes in immunomodulatory therapy for multiple sclerosis in the 6 months before being randomly assigned, glucocorticoid use within 30 days before screening, concurrent use of 4-aminopyridine or fam pridine, 27 or serological evidence of vitamin B12 deficiency or hypothyroidism.…”
Section: Study Design and Participantsmentioning
confidence: 99%